Integrated treatment of suburb diffuse pollution using large-scale multistage constructed wetlands based on novel solid carbon: Nutrients removal and microbial interactions - Jia, Lixia; Qi Zhou; Li, Yuanwei; Wu, Weizhong (JOURNAL OF ENVIRONMENTAL MANAGEMENT, 2023)
In this study, an integrated treatment system was proposed and applied in situ, including detention tank, multistage constructed wetlands (CWs) and wastewater treatment plants (WWTPs), preventing nutrients flowing into Dianchi Lake, in which the treatment performance of multistage CWs were evaluated principally. Results skillfully realized the bypass purification of upstream river at dry reasons, as well as the effective management and treatment of the collected diffuse pollution at rainy reasons. The purified water flowing into water bodies could satisfy the Grade III of environmental quality standards for surface water in China with the average effluent concentrations of COD, NH4+-N, TN and TP decreased to 10 (51.2-72.7%), 0.5 (67.2-83.0%), 1.0 (71.2-79.6%) and 0.15 (72.3-89.4%) mg L-1, respectively. High-throughput sequencing results indicated that the application of poly-3-hydroxybutyrate-cohyroxyvelate-sawdust (PS) blends could enrich norank_f_Anaerolineaceae (7.95%) and Bradyrhizobium (10.2%), which were distinct from the dominant genera of Pleurocapsa (13.0%) in gravel -based CWs. Functional genes and metabolism analysis uncovered that the heterotrophic denitrification was the main pathway of nitrogen removal with the abundance of genes encoding TCA cycle, glycolysis and deni-trification process up-regulated. In addition, molecular ecological network (MEN) analysis suggested the deni-trification genes were positively correlated with the predominant microbes in PS-based CWs, favorable for denitrifiers to transfer and utilize electron donors during denitrification process. This study proved that the developed PS blends as carbon supplies in CWs and the proposed integrated treatment system are effective methods for watershed management, providing valuable reference to low-pollution wastewater treatment in practical engineering projects.